Application of Adomian Method for the Magnetic field effects on mass transport at vertical cylindrical electrode. (1st December 2015) - Aaboubi, O.; Hadjaj, A.; Ali Omar, A.Y.
Abstract: Magnetic forced convective mass transfer onto cylindrical electrode placed in a uniform horizontal magnetic field is considered. The study is based on polarization curves and chronoamperometry measurements during oxidation or reduction of ferri-ferrocynide system at various bulk concentrations. In the case of platinum electrode with different diameter and cylinder length, the obtained results show an increase of the mass transfer rate similar to that observed on horizontal or vertical flat plates. The enhancements of the limiting diffusion current depend on the magnetic field strength; the bulk electroactive species concentration and cylindrical electrode diameter and length have been quantified. Based on Adomian decomposition method (ADM), a detailed theoretical analysis of the mass transfer process is undertaken, and expressions are obtained which predict with good accuracy the observed experimental data.